Ocular Nocardiosis: A Case Report. (3rd October 2019) - Angermann, Reinhard; Stattin, Martin; Zehetner, Claus
ABSTRACT: Purpose : To describe the challenging diagnosis of ocular nocardiosis in a patient with anaplastic astrocytoma Methods : A 56-year-old patient with recurrent cerebral anaplastic astrocytoma and a history of surgical resection, who underwent radiotherapy and chemotherapy, presented with a unilateral white subretinal mass at the posterior pole of his left eye. Vitrectomy and fine-needle biopsy of the vitreous as well as the subretinal mass were performed. Results : Magnetic resonance imaging verified progression of the lesion's size at follow-up. Histopathological workup of the material revealed gram-positive filamentous bacteria consistent with Nocardia cyriacigeorgica . Conclusion : Endogenous Nocardia should be suspected in case of choroidal abscess in immunocompromised patients. Clinical diagnosis is challenging; therefore, early subretinal biopsy should be considered to facilitate treatment decision.